Insights into triterpene synthesis and unsaturated fatty-acid accumulation provided by chromosomal-level genome analysis of Akebia trifoliata subsp. australis. (1st February 2021) - Huang, Hui; Liang, Juan; Tan, Qi; Ou, Linfeng; Li, Xiaolin; Zhong, Caihong; Huang, Huilin; Møller, Ian Max; Wu, Xianjin; Song, Songquan
Abstract: Akebia trifoliata subsp. australis is a well-known medicinal and potential woody oil plant in China. The limited genetic information available for A. trifoliata subsp. australis has hindered its exploitation. Here, a high-quality chromosome-level genome sequence of A. trifoliata subsp. australis is reported. The de novo genome assembly of 682.14 Mb was generated with a scaffold N50 of 43.11 Mb. The genome includes 25, 598 protein-coding genes, and 71.18% (485.55 Mb) of the assembled sequences were identified as repetitive sequences. An ongoing massive burst of long terminal repeat (LTR) insertions, which occurred ~1.0 million years ago, has contributed a large proportion of LTRs in the genome of A. trifoliata subsp. australis . Phylogenetic analysis shows that A. trifoliata subsp. australis is closely related to Aquilegia coerulea and forms a clade with Papaver somniferum and Nelumbo nucifera, which supports the well-established hypothesis of a close relationship between basal eudicot species. The expansion of UDP-glucoronosyl and UDP-glucosyl transferase gene families and β-amyrin synthase-like genes and the exclusive contraction of terpene synthase gene families may be responsible for the abundant oleanane-type triterpenoids in A. trifoliata subsp. australis . Furthermore, the acyl-ACP desaturase gene family, including 12 stearoyl-acyl-carrier protein desaturase ( SAD ) genes, has expanded exclusively. A combined transcriptome and fatty-acid analysis of seeds at five developmental stages revealed that homologs of SADs, acyl-lipid desaturase omega fatty acid desaturases (FADs), and oleosins were highly expressed, consistent with the rapid increase in the content of fatty acids, especially unsaturated fatty acids. The genomic sequences of A. trifoliata subsp. australis will be a valuable resource for comparative genomic analyses and molecular breeding.